2004
DOI: 10.1164/rccm.200402-232oc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tuberculin Skin Test and New Specific Blood Test in Tuberculosis Contacts

Abstract: The tuberculin skin test used to detect latent Mycobacterium tuberculosis infection has many drawbacks, and a new diagnostic test for latent tuberculosis (QuantiFERON-TB [QTF-TB]) has recently been introduced. This test measures the production of IFN-gamma in whole blood upon stimulation with purified protein derivative (PPD). The QTF-TB test addresses the operational problems with the tuberculin skin test, but, as the test is based on PPD, it still has a low specificity in populations vaccinated with the Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
251
2
15

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(289 citation statements)
references
References 14 publications
21
251
2
15
Order By: Relevance
“…It has been previously reported that in vitro whole blood IFN-γ response to PPD correlates well with TST (Black et al, 2001). We found poor agreement between QuantiFERON® and PPD tests in all groups, which is consistent with other reports (Brock et al, 2001(Brock et al, & 2004Mori et al, 2004;Kang et al, 2005) and confirms that QuantiFERON® test is substantially more specific than TST in BCG vaccinated persons. Brock and co-workers (2004) showed that, in BCG-vaccinated persons, 50 % of high-exposure and 6 % of lowexposure group responded to QuantiFERON®, which gives the similar overall prevalence to those of the unvaccinated subjects, 53 % and 5 %, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been previously reported that in vitro whole blood IFN-γ response to PPD correlates well with TST (Black et al, 2001). We found poor agreement between QuantiFERON® and PPD tests in all groups, which is consistent with other reports (Brock et al, 2001(Brock et al, & 2004Mori et al, 2004;Kang et al, 2005) and confirms that QuantiFERON® test is substantially more specific than TST in BCG vaccinated persons. Brock and co-workers (2004) showed that, in BCG-vaccinated persons, 50 % of high-exposure and 6 % of lowexposure group responded to QuantiFERON®, which gives the similar overall prevalence to those of the unvaccinated subjects, 53 % and 5 %, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…TST is also likely to be a good indicator of latent infection in a population of BCG-unvaccinated subjects but is confounded by BCG vaccination (Brock et al, 2004). In the present study, we demonstrated that QuantiFERON® test kit clearly differentiated the BCG-vaccinated healthy individuals at low risk of exposure from TB patients in contrast to the results obtained using only PPD.…”
Section: Discussionmentioning
confidence: 47%
“…Compared with the TST, research using IFNGRA indicates a high sensitivity for active tuberculosis (8)(9)(10). Positive scores in these assays have also been shown in contact studies to equate well with a history of exposure to tuberculosis (11)(12)(13).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 75%
“…This was observed regardless of the cutoff point for CD4 ϩ cell count. With T-SPOT.TB, 48% (25), 54% (13), and 44% (9) at CD4 ϩ cell count Ͻ 350, Ͻ 250, and Ͻ 200/mm 3 , respectively, were identified as positive and QFT-G identified 33% (24), 33% (12), and 26%, respectively (Figure 4). Tests for trend were, however, not statistically significant.…”
Section: Stratification Of Results In Hiv-infected Persons By Cd4 ؉ Cmentioning
confidence: 99%
“…Conversely, HLA-DR4-restricted Ag85B epitopes may -in addition to MTB diagnosis -be useful to enumerate T cells specific for Mycobacterium ulcerans, the causative agent of Buruli ulcer [29] or M. avium intracellulare, a frequent cause for infections in immunecompromised patients. In addition, while novel assays, such as the IFN-c response assay (IGRA) [27,[30][31][32], address some of the weaknesses of the TST by using specific antigens in peptide form, they do not allow the simultaneous analysis of T-cell responses and T-cell marker analysis associated with T-cell homing and differentiation, as is demonstrated here. The use of a broader panel of MTB-and MOTT-associated antigens may aid in dissecting the precise targets of CD4-and CD8-mediated immune responses in MTB patients undergoing therapy (and therefore, potentially alterations in bacterial load).…”
Section: Discussionmentioning
confidence: 99%